The Influence of Management Accounting Information System Characteristics and Management Control System on Managerial Performance - Nuraliati, Ayke; Sriwardani, Sriwardani; Laraswati, Elis (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
Several things that can affect and improve managerial performance at PT Warna Indah Samajaya (WIS), one of which is the characteristics of the management accounting information system and management control system. The characteristics of the management accounting information system that have been carried out by employees of PT Warna Indah Samajaya (WIS) have been implemented properly and correctly to carry out effective work so that they can achieve the predetermined targets. This study aims to determine the effect of the characteristics of the management accounting information system and control system on managerial performance at PT Warna Indah Samajaya (WIS). This research was conducted by means of a survey by distributing questionnaires to employees of PT Warna Indah Samajaya (WIS), this study also used a verification descriptive analysis method by statistically processing using SEM-PLS. The results of this research are expected to be a solution in solving problems of managerial performance at PT Warna Indah Samajaya (WIS). The results of this study indicate that: (1) the characteristics of the accounting information system affect managerial performance, (2) the control system has an effect on managerial performance.